Quantifying ecosystem services: role of commons in supporting food systems - Sandhu, Harpinder (2021)
Harpinder Sandhu SPECIAL EVENT UNFSS Science Days Side Event: Promise of the Commons for Sustainable and Equitable Food Systems Co-organized by International Food Policy Research Institute (IFPRI); Foundation for Ecological Security (FES, India); University of South Australia; Azim Premji University and the CGIAR Research Program on Policies, Institutions, and Markets (PIM) JUL 7, 2021 - 07:00 AM TO 08:00 AM EDT